Methionine‐Restricted Diet Increases miRNAs That Can Target RUNX2 Expression and Alters Bone Structure in Young Mice. Issue 1 (22nd June 2016) - Plummer, Jason; Park, Miri; Perodin, Frantz; Horowitz, Mark C.; Hens, Julie R.
ABSTRACT: Dietary methionine restriction (MR) increases longevity and improves healthspan in rodent models. Young male C57BL/6J mice were placed on MR to assess effects on bone structure and formation. Mice were fed diets containing 0.86% or 0.12% methionine for 5 weeks. Fasting blood plasma was analyzed for metabolic and bone‐related biomarkers. Tibiae were analyzed by histomorphometry, while femurs were analyzed by micro‐CT and biomechanically using 4‐point bending. MR mice had reduced plasma glucose and insulin, while FGF21 and FGF23 increased. Plasma levels of osteocalcin and osteoprotegrin were unaffected, but sclerostin and procollagen I decreased. MR induced bone marrow fat accretion, antithetical to the reduced fat depots seen throughout the body. Cortical bone showed significant decreases in Bone Tissue Density (BTD). In trabecular bone, mice had decreased BTD, bone surface, trabecula and bone volume, and trabecular thickness.. Biomechanical testing showed that on MR, bones were significantly less stiff and had reduced maximum load and total work, suggesting greater fragility. Reduced expression of RUNX2 occurred in bone marrow of MR mice. These results suggest that MR alters bone remodeling and apposition. In MR mice, miR‐31 in plasma and liver, and miR‐133a, miR‐335‐5p, and miR‐204 in the bone marrow was elevated. These miRNAs were shown previously to target and regulate Osterix and RUNX2 in bone, which could inhibit osteoblast differentiation and function. Therefore, dietary MR in young animals alters bone structure by increasing miRNAs in bone and liver that can target RUNX2. J. Cell. Biochem. 118: 31–42, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Dietary methionine restriction (MR) in young mice results in alter microarchitecture of the bones. MR causes changes in miRNAs that can target RUNX2 in osteoblasts and osteoblast progenitor cells that results in reduced activity in the bones.